STRENGTHENING GLOBAL GOVERNANCE: INDONESIA’S COURT AND THE CENTRAL KALIMANTAN FOREST FIRE CASE - Ary Aprianto (Faculty of Law Universitas Lampung, 2021)
The success of global governance depends on the coherency of efforts of its actors, notably states. States are expected to meet their international obligation, including through their domestic policies. As a member of the international community, Indonesia has become a party to numerous treaties and participated in various effort to address global challenges. Yet reference to international law by Indonesia’s domestic court has so far been justified only for the sake of improving the quality of judgment or maintaining Indonesia’s standing as a law-abiding state. Further, most Indonesia’s legal scholars focus their attention on the position of international law in the domestic legal hierarchy, and how monism and dualism approaches influence the implementation of international law at the national level. This article focuses on how domestic court judgments have impacts outside national borders. It employs a normative research method, and uses the Central Kalimantan Forest Fire case as the stepping-stone of discussion. It concludes that the application of international law by Indonesia’s domestic court supports the intention of delivering a high quality judgment and strengthening the global governance.